Benthic Foraminifera Distribution in the Sediment of Western Part of the Horizontal Section In Rupat Strait - ', Rosshalia; ', Rifardi; ', Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted in May 2014 in the western part of the RupatStrait Riau Province with its aims to determine the distribution of benthicforaminifera and sedimentation relative velocity. The determination of samplingpoints was done by using purposive sampling method. The sediments were taken byusing Eckman Grab then preserved with Rose Bengal mixed by formalin .The results showed that benthic foraminifera was found in higher amounts inthe north and south of the study site. By contrast, the smaller number was found inthe middle of the strait and the shoreline with the mangrove. These areas werepredominantly influenced by the high flow of current and mangrove area, withrelatively moderate sedimentation velocity. In West Rupat the waters was dividedinto 3 clusters based on the data distribution of benthic species foraminefera namely:group I was found in the northern, central and southern part of the study sites,characterized by dominating species of Reussella hayasakai, Textularia orbica andBolivina humilis and sediment classified as very fine sand; group II was found in thenorthern part of the study site with species that as dominated wereFissuripolymorphina aequicellaris, Rosalina Concina and Bolivina humilis with highorganic matter content in the study sites; group III was found in the southern part ofresearch location with the dominating species were Ammonia beccari, Textulariaarticulata and Textularia neoconica with the bottom sediments belonging to very finesand.Keywords : benthic foraminifera, sediment, Rupat Strait..